Peran Guru Kelas dalam Mengembangkan Keterampilan Berbahasa Siswa Kelas Rendah - Wulan Dhari, Putri; Anggraini, Heni; Nasution, Mustafa Kamal (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
The study was conducted to find out, describe, and explore data on the role of teachers in developing the language skills of low-grade students at MIN 12 Aceh Tengah, as well as the obstacles faced by teachers in the process. This type of research is descriptive qualitative using case study method that is natural setting. Data sourced from MIN 12 Aceh Tengah teachers with data collection techniques through observation, interviews, and document analysis. Some of the roles of teachers in developing the language skills of low-grade students in MIN 12 Aceh Tengah are; 1) as mentors and educators, teachers train, educate, guide, and teach students using a good and correct Bahasa; 2) as demonstrators and motivators, teachers can provide understanding in Indonesian language learning, are required to have exemplary qualities, and motivate students in learning; 3) as a mediator, teachers provide the right tools to support the success of the learning process; 4) as a facilitators, teachers become providers of all students’ needs in learning Bahasa; and 5) as a evaluators, teachers reflect, assess, and measure the extent of students' language skills.